A prospective cohort study of the relationship between the withdrawal time and the detection rate of colorectal adenoma. (2nd September 2022) - Zhao, Min; Xu, Ying; Zhu, Haijing; Chen, Jiaying; Sun, Weijie; Yang, Daming; Peng, Haixia
Abstract: Background and aims: The effect of colonoscopy withdrawal time (WT) beyond 6 min on colorectal adenoma detection rate (ADR) is unclear. We focused on the relationship between WT and ADR. Materials and methods: This study was a prospective observational study involving 437 patients who underwent colonoscopy at Tongren Hospital in Shanghai from 1 July 2020 to 31 August 2020. Patients were divided into two groups according to whether the WT was >6 min. Age, sex, body mass index (BMI), defoaming rate score, Boston bowel preparation scale (BBPS), primary colonoscopy, hypertension, diabetes mellitus, dietary preparation 1 day before the examination, and abdominal surgery history factors were analysed by univariate and multivariable logistic regression to explore the odds ratios (ORs) of ADR in two WT groups. Restricted cubic spline regression was used to further analyze the relationship between WT and the ORs of adenoma detection. Results: The ADR among 437 patients was 17.16% (75/437). Multivariable regression analysis showed that in the group with WT >6 min, patients aged ≥50 years old and male could have an increased risk of adenoma detection (OR 5.80, 95% CI 2.32–14.47; p  < .001; OR 2.30, 95% CI 1.19–4.43; p  = .013). The cubic spline curve showed that the ADR increased with time for WT of 6–8 min, and the highest ADR was achieved when the WT was controlled at 8 min (WT = 5.997, OR = 0.997; WT = 8.240 min, OR = 3.092). Conclusion: The highest ADR was achieved when the WT of colonoscopy was controlled at 8 min.